Critical Illness Polyneuropathy: a multicenter study on functional outcome - Syneonidou, Zaira P.; Theorodaki, Kassiani; Chalkias, Athanasios; Argyra, Erifili; Casale, Roberto (Giornale Italiano di Medicina del Lavoro ed Ergonomia, 2025)
Objective. To describe the functional recovery of consecutive inpatients with Critical Illness Polyneuropathy (CIP) at the time-point of the discharge from rehabilitation units according to Barthel Index scores. To examine whether age, gender, pre-ICU admission diagnosis, tracheostomy performance, heterotopic ossification development and duration of neuro-rehabilitation treatment are among the prognostic factors that can predict the functional outcome in studied patients.Design. A retrospective observational clinical study from January 2010 to December 2014. Three rehabilitation units in Greece.Results. Sixteen subjects (57.1%) had >60 Bl discharge scores, showing a prospect in gaining further independence. Females presented a tendency for better functional outcome vs males (73.8±12.6 vs 58.6±23.4, p=0.082). Respiratory, septic and neurologic patients demonstrated better rates of functional improvement after the rehabilitation process vs cardiac patients (p